Analisis kemandirian belajar pada masa pembelajaran daring siswa kelas V sekolah dasar - Lutfi Anugerah, Elga Pramesti; Mahfud, Hasan; Matsuri, Matsuri (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
Abstract. Independent learning is a learning activity that is carried out independently to achieve goals and a good learning process. This is done by students so that they start themselves not to depend on others with a variety of materials. This type of research is a qualitative researcher with a case study method. The subjects in this study were the parents of class V Purwotomo No.97 Surakarta as many as 12 students to be studied. The data analysis used in this research is an interactive analysis technique using the Miles and Huberman model. The results of this study indicate that the independence of learning material diversity in Indonesia for fifth grade students at SDN Purwotomo during the online learning period can be implemented, and it can be concluded that students' learning independence is still less independent. In the five indicators of student learning independence, namely not depending on others, having a responsible attitude towards himself, being able to behave on his own initiative, cannot be said to be independent because it is 60.00%, while having learning independence. Confident and able to behave in a disciplined manner are said to be independent because they are already independent. reached 60.00%..